A phase I/II study of sorafenib in combination with low dose cytarabine in elderly patients with acute myeloid leukemia or high-risk myelodysplastic syndrome from the National Cancer Institute of Canada Clinical Trials Group: trial IND.186. Issue 4 (April 2013) - Macdonald, David A.; Assouline, Sarit E.; Brandwein, Joseph; Kamel-Reid, Suzanne; Eisenhauer, Elizabeth A.; Couban, Stephen; Caplan, Stephen; Foo, Alison; Walsh, Wendy; Leber, Brian
Abstract Sorafenib is active in patients with acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). The National Cancer Institute of Canada (NCIC) Clinical Trials Group initiated a phase I/II study of the combination of sorafenib with cytarabine in older patients with AML or high-risk MDS who were unsuitable for intensive chemotherapy. FLT3 mutational status was determined in all patients. Twenty-one patients were enrolled (four MDS, 17 AML) with a median age of 77 years. The recommended phase II dose (RP2D) was cytarabine 10 mg bid days 1–10 and sorafenib 600 mg/day days 2–28. Dose-limiting toxicities were fatigue, sepsis and skin rash. Of 15 evaluable patients treated at the RP2D, two patients responded. The overall response rate for eligible patients was 10%. FLT3 mutations were found in only three patients. We conclude that this combination of sorafenib and cytarabine has limited activity in this unselected cohort of elderly patients with AML/MDS in which FLT3 mutations seemed underrepresented.